[Spanish translation] Joint associations of moderate-to-vigorous physical activity and smartphone screen time with inhibitory control performance in adolescents - Gomes, Romilton Victal (2025)
This cross-sectional study investigated the joint associations of moderate-to-vigorous physical activity (MVPA) and smartphone screen time (ST) with inhibitory control performance in 210 Brazilian school adolescents. MVPA level was assessed using the Global School-based Student Health Survey questionnaire, categorized as inactive (<60 min/day) or active (60+ min/day). Weekly ST was measured using participants’ smartphones, categorized as low (<7 h/day) or high (7+ h/day) based on the median. Participants were divided into four groups: inactive + high ST, inactive + low ST, active + high ST, and active + low ST. Inhibitory control performance was evaluated using the Flanker task, measuring reaction time and accuracy in congruent/incongruent stimulus. A generalized multiple gamma model revealed that only the inactive + high ST group showed a higher reaction time in the incongruent phase compared to the active + low ST group (β = 41.1 ms; 95% CI 2.3, 79.9; p = .038). No differences were found in the accuracy (p > .05). In conclusion, physical inactivity combined with high smartphone ST is associated with poorer inhibitory control performance in school adolescents.